2007
DOI: 10.1111/j.1467-9604.2007.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

IEPs in mainstream secondary schools: an agenda for research

Abstract: Providing children with special educational needs with individual education plans (IEPs) was advocated in the 1994 code of practice for SEN, and retained in the 2000 code. Specifically as it relates to mainstream secondary schools, this has proved highly controversial: many SENCos report that the writing and implementing of IEPs is a bureaucratic encumbrance, whilst others, going about the process of writing IEPs in very different ways, report that the process is both manageable and beneficial to the children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Research has demonstrated that there are difficulties connected to IDP and IEP plans, such as imprecise wording in documents, problems with organizing the process of documentation, and a lack of consensus on how the plan relates to improving learning and raising achievement (Tennant, 2007;Hirsch, 2014). There are also studies pointing to positive effects if the number of targets is kept down, if all parties concerned -teachers, special educators, parents and students -are involved in the process and if there is a belief among staff that IEPs and IDPs can actually make a difference, then IEP and IDP work can be seen as good practice (Tennant, 2007;Hirsch, 2014).…”
Section: An Organizational Approach To Documentation Of Special Educamentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that there are difficulties connected to IDP and IEP plans, such as imprecise wording in documents, problems with organizing the process of documentation, and a lack of consensus on how the plan relates to improving learning and raising achievement (Tennant, 2007;Hirsch, 2014). There are also studies pointing to positive effects if the number of targets is kept down, if all parties concerned -teachers, special educators, parents and students -are involved in the process and if there is a belief among staff that IEPs and IDPs can actually make a difference, then IEP and IDP work can be seen as good practice (Tennant, 2007;Hirsch, 2014).…”
Section: An Organizational Approach To Documentation Of Special Educamentioning
confidence: 99%
“…There are also studies pointing to positive effects if the number of targets is kept down, if all parties concerned -teachers, special educators, parents and students -are involved in the process and if there is a belief among staff that IEPs and IDPs can actually make a difference, then IEP and IDP work can be seen as good practice (Tennant, 2007;Hirsch, 2014).…”
Section: An Organizational Approach To Documentation Of Special Educamentioning
confidence: 99%
“…Podobné problémy s dokumentací vzešlé z ro-dičovských schůzek jako ve Švédsku přitom vykazují například také rodičov-ské schůzky v Británii, z nichž vycházejí dokumenty IEP (Tennant, 2007). Irská studie v této souvislosti poukázala na to, že žáci i rodiče se méně zapojují, je-li dokumentace složitá (Prunty, 2011).…”
Section: Mezinárodní Srovnáníunclassified
“…V jiných evropských zemích je rodič zpravidla informován učitelem (Hirsh, 2012;Tennant, 2007) a evaluace dokládají, že učitelé se často uchylují k mechanickým zjednodušením a hodnoticím metodám (Gross, 2000;sEn-…”
Section: Evropská Perspektivaunclassified
“…The use of Individual Education Plans (IEPs) as a means of managing educational provision for students deemed to have special educational needs was introduced in the UK in the 1994 Code of Practice for special educational needs (DfEE, 1994) and restated in the revised Code (DfES, 2001). Specifically in a mainstream secondary school context, as considered in Tennant (2007), this has been a hugely contentious area: whilst SENCos can be found who are confident that they have manageable systems to write and implement IEPs which operate in the best interests of the student with special educational needs, concern has been expressed that considerable resources are being used to produce IEPs which detract from special educational needs provision.…”
Section: Introductionmentioning
confidence: 99%